HUBUNGAN PENGETAHUAN, SIKAP DAN PENYULUHAN KESEHATAN DENGAN PEMBERANTASAN SARANG NYAMUK DEMAM BERDARAH DENGUE (PSN-DBD) DI KELURAHAN SIMPANG III SIPIN KECAMATAN KOTA BARU KOTA JAMBI - , Alidan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Dengue hemorrhagic fever (DHF) is a public health problem that can lead to social and economic impact. Jambi Municipality as a highest contributor to the incidence of dengue hemorrhagic fever (DHF) compared to the other regencies/ municipalities in Jambi Province. The DHF highest endemic area in Jambi Municipality was Simpang III Sipin Subdistrict, was include in the work area of Rawasari Public Health Center (PHC) with the number of incidence was 31 incidences. Objectives: To knowing the correlation between knowledge, attitude, health elucidation, periodic mosquito larvae inspection with Dengue Hemorrhagic Fever (DHF) mosquito breeding place eradication in Simpang III Sipin, Jambi Municipality. Methods: This was observational study by used cross sectional design. The population was the family leader in the household with DHF incidence in Simpang III Sipin Subdistrict, Jambi Municipality. The sampling was performed used systematic random sampling. Results: The public in Simpang III Sipin, Jambi Municipality (63.3%) had good behavior in DHF mosquito breeding place eradication. There was significant correlation between knowledge, attitude, health elucidation, periodic mosquito larvae inspection with DHF mosquito breeding place eradication implementation (p value< 0.05). Periodic mosquito larvae inspection was the variable which provides greatest influence to the DHF mosquito breeding place eradication implementation. Conclusion: The greatest influence and can be used to predict the DHF mosquito breeding place eradication implementation was periodic mosquito larvae inspection.